Sun’iy intellektning elektron (raqamli) hukumatga ta’siri: muammolar va imkoniyatlar - Abdullayev Shohzod Xayrulla o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article analyzes the impact of artificial intelligence on electronic (digital) government, the opportunities it presents and the potential problems it may cause.